2002
DOI: 10.1093/jn/131.10.3151
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Intake of trans (n-3) Polyunsaturated Fatty Acids Reduces the b-Wave Amplitude of Electroretinograms in Rats

Abstract: Weanling rats were fed three diets differing in their concentrations of the cis- and trans-isomers of alpha-linolenic acid [18:3(n-3)] for 12 mo to study the long-term effects of these fatty acids on the electroretinogram (ERG). The diets contained 18:3(n-3) in its natural form at 2.0 g/100 g total fatty acids (C group), partially isomerized 18:3(n-3) [1.3 g/100 g cis 18:3(n-3) + 0.7 g/100 g trans 18:3(n-3); cT group] and the control level of cis 18:3(n-3) with trans 18:3(n-3) [2.0 g/100 g cis 18:3(n-3) + 0.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…In rats deprived from n-3 PUFA from 2 generations, the main finding concerning the retinal function was the decreased ERG a-wave and b-wave amplitudes. We already demonstrated that the isomerization of dietary α-linolenic acid decreased the ERG b-wave amplitude in rats [26,44]. Considering the typical pattern of retinal fatty acids (as described above), the defects observed here in the retinal function may be mainly the consequence of the decreased dietary intake of cis α-linolenic acid and subsequently the lack of cis DHA.…”
Section: Retinal Phospholipidssupporting
confidence: 69%
“…In rats deprived from n-3 PUFA from 2 generations, the main finding concerning the retinal function was the decreased ERG a-wave and b-wave amplitudes. We already demonstrated that the isomerization of dietary α-linolenic acid decreased the ERG b-wave amplitude in rats [26,44]. Considering the typical pattern of retinal fatty acids (as described above), the defects observed here in the retinal function may be mainly the consequence of the decreased dietary intake of cis α-linolenic acid and subsequently the lack of cis DHA.…”
Section: Retinal Phospholipidssupporting
confidence: 69%
“…The second group of thirty-four male Wistar rats (14 weeks old, 450-550 g body weight) was fed a n-3 PUFA deficient diet (n-3-depleted animals). These animals were issued from two generations of rats fed the n-3 PUFA deficient diet (13). All animals had ad libitum access to food and water.…”
Section: Methodsmentioning
confidence: 99%
“…The data are reported in g/100 g of diet. The extended composition of the mineral and vitamin mixes has been reported elsewhere (Acar et al, 2002).…”
Section: Animal Experimentsmentioning
confidence: 99%